Micro-Edm:Overview And Recent Developments - Mahendran, Samykano (2010)
Micro-EDM is a process based on the thermoelectric energy between the workpiece and an electrode. Micro-EDM is a newly developed method to produce micro-parts which in the range of 50 μm -100 μm. Micro-EDM is an efficient machining process for the fabrication of a micro-metal hole with various advantages resulting from its characteristics of non-contact and thermal process. A pulse discharges occur in a small gap between the work piece and the electrode and at the same time removes the unwanted material from the parent metal through the process of melting and vaporization. This paper describes about the principles, recent developments, parameters for material removal rate and the tool wear rate that are essential in the Micro-EDM process.